Aplicação de quitosana para controle microbiológico em queijo colonial artesanal - Carneiro, Gabriel Bortolotto (2021)
The production of artesanal Colonial cheese has great social and cultural influence in the southern region of Brazil. However, the use of raw milk and deficiencies in Good Manufacturing Practices can contribute to the occurrence of contamination by microorganisms such as coliforms and Staphylococcus in the product. The aim of this study was to evaluate the applicability of chitosan incorporated into the curds as a microbiological control in artisanal Colonial cheese. The cheeses were produced with raw milk in a cheese factory located in the rural area of Francisco Beltrão - PR. After the step of draining and salting, four kilograms were separated for the control samples, and in the other four kilograms, chitosan was added. Physicochemical analyzes of moisture, total solids and acidity, and microbiological analyzes of coagulase-positive Staphylococcus, total and thermotolerant coliforms and lactic acid bacteria were performed. According to the results, the addition of chitosan did not interfere with the physicochemical characteristics of the samples. Regarding the microbiological evaluation, all samples showed low values for coagulase-positive Staphylococcus. Thus, it was not possible to determine the influence of chitosan in the development of this microorganism. The 1% concentration of chitosan is shown to be inefficient in inhibiting the development of total coliforms. It was also not possible to evaluate the action of chitosan on thermotolerant coliforms, as the count was low. There was no interference of chitosan in the development of lactic acid bacteria.